Balancing LncRNA H19 and miR‐675 Bioconversion as a Key Regulator of Embryonic Myogenesis Under Maternal Obesity - Yao Gao; Md Nazmul Hossain; Liang Zhao; Xiangdong Liu; Yanting Chen; Jeanene Marie Deavila; Mei‐Jun Zhu; Gordon K. Murdoch; Min Du (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Maternal obesity (MO) impairs fetal skeletal muscle development, but the underlying mechanisms remain poorly defined. The regulatory roles of lncRNA H19 and its first exon derived microRNA675 (miR675) in prenatal muscle development remain to be examined. H19/Igf2 are in the same imprinting cluster with H19 expressed from the maternal allele while Igf2 expresses paternally. H19 contains a G‐rich loop, and KH‐type splicing regulatory protein (KHSRP) mediates the biogenesis of pre‐miRNAs containing G‐rich loops, which depends on its phosphorylation by AKT, a key mediator of IGF2 signalling. This study aims to depict the elusive function of these regulators that are affected by MO during embryonic myogenesis. Methods Single‐cell transcriptomic sequencing and GeoMx spatial RNA sequencing were performed to identify the differentially expressed genes between embryos from MO and control (CT) mice. Both E11.5 and E13.5 embryos were collected and analysed to validate the sequencing data. The roles of H19 and miR657 in myogenesis were further analysed in P19 embryonic cells via CRISPR/dCas9‐mediated H19 activation and inhibition. The epigenetic changes of H19 were analysed by methylated DNA immunoprecipitation, and allele‐targeted analysis of H19 was performed by crossing C57BL/6J and CAST/EiJ mice. Results Transcriptomic analysis showed that MO embryos contained less differentiated myocytes (1.34%) than CT embryos (2.86%). Myogenesis‐related GO biological processes were down‐regulated in the MO embryonic myotome region. MO embryos showed lower expression of myogenic transcription factors such as Myf5, Myod1, Myog, Mef2c and Myh3 (p < 0.05). MO altered epigenetic modifications of the H19 genomic cluster, showing a decreased methylation level in H19 imprinting control region (p < 0.05) and a diallelic expression pattern of H19, which elevated its expression in MO embryos. Overexpression of H19 inhibited myogenesis in P19 cells, but miR675 promoted myogenesis, suggesting the critical regulatory roles of bioconversion of H19 to miR675. A KHSRP mediates the biogenesis of miR675, a process that relies on its phosphorylation by IGF2/AKT signalling. Knocking‐down of KHSRP and inhibition of AKT abolished miR675 biogenesis. MO suppressed IGF2/AKT signalling and blocked KHSRP‐dependent miR675 biogenesis in embryos. Conclusions We found differential effects of H19 and miR675 on embryonic myogenesis. MO up‐regulates H19 but blocks its miR675 bioconversion via suppressing IGF2/AKT/KHSRP signalling axis. Myogenesis in MO embryos was impeded due to the highly accumulated H19 and blocked miR675 biogenesis.